Do the body weight perception and body mass index affect the participation of exercise? - Can Sema; Demirkan Erkan; Çeviker Abdulkerim (Sciendo, 2022)
Study aim: In this study, it is aimed to find out the exercise preferences based on the Body Mass Index (BMI) and Body Weight Perception (BWP), and to determine the consistency between BMI and BWP calculated via the self-reporting method.